2021
DOI: 10.1155/2021/1442093
|View full text |Cite
|
Sign up to set email alerts
|

miR-199a Targeting PNRC1 to Promote Keratinocyte Proliferation and Invasion in Cholesteatoma

Abstract: Introduction. miR-199a has been reported as an oncogene of various cancers. However, the biological function and regulatory mechanism of miR-199a in keratinocytes of cholesteatoma are still unclear. Methods. Detection by qRT-PCR was conducted on miR-199a’s expression in both thirty pairs of cholesteatoma tissues and normal skins. For characterizing the function of miR-199a, this research adopted transwell assay, wound healing assay, and CCK8 assays. Under the support of qRT-PCR, efforts were made to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In total, 118 articles were retrieved through the database search. After applying the search strategy described above, a total of 18 articles were identified that met all inclusion criteria [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. A flow diagram of the detailed study selection process is presented in Figure 1.…”
Section: Search Results Study Characteristics and Study Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 118 articles were retrieved through the database search. After applying the search strategy described above, a total of 18 articles were identified that met all inclusion criteria [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. A flow diagram of the detailed study selection process is presented in Figure 1.…”
Section: Search Results Study Characteristics and Study Qualitymentioning
confidence: 99%
“…All included studies used cholesteatoma tissues for analysis. Additionally, the majority of studies included in vitro experiments on cell lines [30,32,[34][35][36][37][38][39][42][43][44]46,47]. In the Zheng study [46], a mouse model was also used for in vivo testing.…”
Section: Search Results Study Characteristics and Study Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Yao et al analyzed the role of microRNA-199a (miR-199a), a cancer-promoting microRNA, as a probable factor influencing the development of cholesteatoma [ 34 ]. They revealed that miR-199a is upregulated in cholesteatoma tissues, which is thought to promote keratinocyte proliferation, migration, and invasion in this pathology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They revealed that miR-199a is upregulated in cholesteatoma tissues, which is thought to promote keratinocyte proliferation, migration, and invasion in this pathology. PNRC1 was found to be a direct target of miR-199a, with a negative regulatory interrelationship [ 34 ].…”
Section: Literature Reviewmentioning
confidence: 99%